Self as a Cluster of Socio-Cultural Simulacra - Čale Feldman, Lada (Array, 2001)
The paper emphasizes one common aspect of both Simmel's and Pirandello's alleged "postmodernity": the connection of their "feminism" with their strikingly similar, socio-culturally grounded theories of acting/living, namely existing/performing and thus (womanly) overcoming the painful dualisms tearing the (men's) culture apart: mind ans body, emotion and cognition, art and life, actors and onlookers, subject and object, self and its other, within and without.